Player perceptions of athlete leadership and leadership development in an English Premier League football academy - Coker, I.; Cotterill, S. T.; Griffin, J. (Asian Journal of Sport and Exercise Psychology, 2022)
The effective leadership of, and within, sports teams has consistently been highlighted to be an important factor impacting upon a range of outcomes including team performance, and team functioning. However, while there has been an increasing focus on athlete leadership and leadership development in recent years there is little research exploring leadership (rather than leader) development in youth sport. As a result, the aim of this study was to explore athlete perceptions of athlete leadership and the development of athlete leadership skills in a professional football youth academy. Participants were 34 professional football club youth academy players, arranged into 9 focus groups (depending upon age). The data were analyzed using thematic analysis, with six first order themes emerging (Leader behaviors, selection criteria, shared leadership, growth and development, changing environmental constraints, and leader development). The results highlight a good level of awareness of leadership amongst the youth footballers, but also major limitations in the degree to which they felt they were developed as leaders.